2009
DOI: 10.1016/j.ccr.2009.02.011
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Increases Glioma-Initiating Cell Self-Renewal through the Induction of LIF in Human Glioblastoma

Abstract: Glioma-initiating cells (GICs) are responsible for the initiation and recurrence of gliomas. Here, we identify a molecular mechanism that regulates the self-renewal capacity of patient-derived GICs. We show that TGF-beta and LIF induce the self-renewal capacity and prevent the differentiation of GICs. TGF-beta induces the self-renewal capacity of GICs, but not of normal human neuroprogenitors, through the Smad-dependent induction of LIF and the subsequent activation of the JAK-STAT pathway. The effect of TGF-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
427
3
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 491 publications
(457 citation statements)
references
References 51 publications
12
427
3
3
Order By: Relevance
“…As TGF-b suppressed the expression of ABCG2 in other types of cancer cells (Figure 4), it is possible that the percentages of CICs in other types of cancers are also decreased by TGF-b. However, contrary to the present findings for diffuse-type gastric carcinomas, TGF-b was reported to maintain the 'stemness' of glioblastoma-initiating cells (Ikushima et al, 2009;Pen˜uelas et al, 2009). TGF-b also maintains the stem-cell-like properties of leukemiainitiating cells in chronic myeloid leukemia through regulation of AKT activation and FOXO3a localization (Naka et al, 2010).…”
Section: Reduction Of Sp Cells In Gastric Cancer By Tgf-b S Ehata Et Alcontrasting
confidence: 99%
“…As TGF-b suppressed the expression of ABCG2 in other types of cancer cells (Figure 4), it is possible that the percentages of CICs in other types of cancers are also decreased by TGF-b. However, contrary to the present findings for diffuse-type gastric carcinomas, TGF-b was reported to maintain the 'stemness' of glioblastoma-initiating cells (Ikushima et al, 2009;Pen˜uelas et al, 2009). TGF-b also maintains the stem-cell-like properties of leukemiainitiating cells in chronic myeloid leukemia through regulation of AKT activation and FOXO3a localization (Naka et al, 2010).…”
Section: Reduction Of Sp Cells In Gastric Cancer By Tgf-b S Ehata Et Alcontrasting
confidence: 99%
“…7C ). This is in agreement with our previous work in which we showed that TGFβ regulates the ability of neurospheres to initiate tumors ( 3,4 ) and, moreover, the two selected models respond to TGFβ receptor inhibitors (unpublished observations), indicating that in those two tumors the regulation of the TGFβ activity is relevant for cancer progression.…”
Section: Creb1 Regulates the Levels Of Tgfb2 In Patient-derived Xenogsupporting
confidence: 81%
“…A potent immune suppressor, TGFβ at high levels facilitates tumor growth through the inhibition of the anticancer immune response. On the other hand, TGFβ has been shown to promote proliferation, angiogenesis, and invasion through the induction of metalloproteases, to enhance the self-renewal of cancer-initiating cells (CIC), and to mediate metastasis due in part to the induction of an epithelial-to-mesenchymal transition (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, gp130 can be activated by ligands such as IL-6 or leukemia inhibitory factor (LIF), and is crucial for signal transductions in multiple stem cells, including ES and cancer stem cells. [37][38][39] In GSCs, gp130 is critical for the maintenance of the stem celllike phenotype of GSCs (Figures 2f and g). As our study demonstrated that CD9 stabilized gp130 expression, we speculate that CD9 could also affect LIF-stimulated gp130 downstream signal transduction, which warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%